2018
DOI: 10.3390/su10072364
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Impact of Disaster Loans: The Case of Small Businesses after Hurricane Katrina

Abstract: Abstract:The US government provided $2.6 billion of small business administration (SBA) disaster loans to individuals and businesses in Mississippi after Hurricane Katrina in 2005. However, existing literature has not fully explored the firm-level effects of post-disaster loan aid, specifically, the effect on small businesses. The objective of this article is to examine whether SBA disaster loans played a significant role in the performance of small businesses after Hurricane Katrina. Data from a sample of 287… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
1
15
1
1
Order By: Relevance
“…Furthermore, simply getting a loan or other financial assistance after the disaster did not necessarily help small businesses, it simply added to their debt load. Hiramatsu and Marshall ( 2018 ) also found a negative relationship between post-Katrina cash flow problems and post-Katrina success.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, simply getting a loan or other financial assistance after the disaster did not necessarily help small businesses, it simply added to their debt load. Hiramatsu and Marshall ( 2018 ) also found a negative relationship between post-Katrina cash flow problems and post-Katrina success.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 97%
“…Also, if strong storm damage was incurred, even businesses without pre-Katrina cash flow problems may begin to experience issues when trying to recover. Hiramatsu and Marshall ( 2018 ) found that even eight years following Katrina, many businesses were struggling to recover. Furthermore, simply getting a loan or other financial assistance after the disaster did not necessarily help small businesses, it simply added to their debt load.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…In a study of the application process for federal disaster loans following Hurricane Katrina, Josephson and Marshall (2016) found that women owners were more likely to apply for disaster loans but, on average, received lower amounts. Hiramatsu and Marshall (2018) found that receiving a small business administration (SBA) disaster loan after Hurricane Katrina played a positive and statistically significant role in determining the actual revenue change and owner perception of revenues, but only for male owners.…”
Section: Business Models and Gendered Crisis Response: What Does The mentioning
confidence: 99%
“…Davlasheridze, Fisher-Vanden, and Allen Klaiber (2017) found FEMA's disaster relief programmes to be effective in mitigating property losses, and Haynes et al (2019) note that it is more probable that businesses receiving SBA disaster loans will flourish in the long run. However, Webb, Tierney, and Dahlhamer (2002), Haynes, Danes, and Stafford (2011), and Hiramatsu and Marshall (2018) discovered no evidence of federal aid helping to improve long-term business recovery outcomes. This conclusion may stem from the fact that businesses that receive disaster relief aid also tend to suffer more economic losses and thus are worse off in the first place due to property damage caused by a disaster.…”
Section: Introductionmentioning
confidence: 99%